Hubungan Tingkat Pendidikan, Pengetahuan dan Dukungan Keluarga Dengan Kepatuhan Dalam Pembatasan Asupan Cairan Pada Pasien Gagal Ginjal Kronik yang Mejalanii Hemodialisa Rawat Jalan di RSUD Sukoharjo - Umayah, Eti (2016)
INTRODUCTION :The success of HD treatment depends on patient compliance, including compliance with fluid intake restriction. Education level, knowledge and family support are some the factors that can improve patientcompliance on dietary restriction of fluids intake. OBJECTIVE: To determain the relationship betwen education level, knowledge, family support and compliance on fluid intake in patients with chronic kidney disease undergoing hemodialysis out patients in Sukoharjo General Hospital. METHODS: Observational study with cross sectional design with a sample of 31 people was performed. Data on education level, knowledge, family support were obtained through direct interview using questionnaire. Compliance data obtained from the percentage of weight gain recorded during observational. Education level was not normally distributed and analysed using Spearman Rank Test, while knowledge and family support data normally distributed and analysed using Pearson Produck so Moment Test. RESULTS: Most respondent have primary education with percentage 74.19%, 58.06% of them have knowledge, 58.06% of respondents have a good family support, and 54.84% of respondents adhere to restrictions on fluid intake. P velue of relationship between level of education and compliance restrictions on fluid intake was 0.019, knowledgeand compliance restrictions on fluid intake was 0.002, family support and compliance restrictions on fluid intake was 0.0047 CONCLUSION: There is a relationship between education level, knowledge,family support and adherence to restrictions on fluid intake in chronic kidney disease patients undergoing hemodialysis in Sukoharjo General Hospital.